2020
DOI: 10.1177/0284185119897351
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analyses of MRI findings for predicting osteomyelitis of the foot in diabetic patients

Abstract: Background There have been no previous magnetic resonance imaging (MRI) studies using multivariable analysis to diagnose osteomyelitis in patients with diabetic foot. Purpose To retrospectively investigate the MRI findings of osteomyelitis in patients with diabetic foot using multivariate analyses. Material and Methods From November 2015 to March 2018, 118 patients who underwent MRI of the foot to evaluate suspected osteomyelitis were included in this study. The patients were categorized into the presence or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
10
0
3
Order By: Relevance
“…If osteomyelitis was suspected because of a positive probe-to-bone test and/or the presence of clinical symptoms, conventional radiographs (cortical erosions or destruction without prior surgery or trauma) and magnetic resonance imaging (MRI; bone marrow suppression on T1-weighted images, bone marrow edema in a fluid-sensitive MR sequence) were performed. 24 , 25 , 29 In case of MRI contraindications, bone scintigraphy or 18F-fluorodeoxyglucose positron emission tomographic / computed tomographic scans were used instead. Intraoperative biopsy of the affected bone was further used to confirm the diagnosis and to acquire a microbiologic profile.…”
Section: Methodsmentioning
confidence: 99%
“…If osteomyelitis was suspected because of a positive probe-to-bone test and/or the presence of clinical symptoms, conventional radiographs (cortical erosions or destruction without prior surgery or trauma) and magnetic resonance imaging (MRI; bone marrow suppression on T1-weighted images, bone marrow edema in a fluid-sensitive MR sequence) were performed. 24 , 25 , 29 In case of MRI contraindications, bone scintigraphy or 18F-fluorodeoxyglucose positron emission tomographic / computed tomographic scans were used instead. Intraoperative biopsy of the affected bone was further used to confirm the diagnosis and to acquire a microbiologic profile.…”
Section: Methodsmentioning
confidence: 99%
“…LR is a frequently used approach for predicting DFU infections [ 28 , 29 ]. Furthermore, efforts have been made to establish a prediction model for NF and OM using LR [ 30 , 31 ]. Likewise, we could establish the classification model for DFU infections using LR based on the ML technique.…”
Section: Methodsmentioning
confidence: 99%
“…Infected bone should have bone marrow oedema signal on fluid-sensitive images, and confluent low signal on T1W images ( Figures 18B - D ). Recent studies have shown that in patients with diabetic foot ulcers, bone marrow oedema with increased signal on fluid-sensitive sequences and preserved T1W signal frequently progresses to osteomyelitis, especially in ulcers larger than 3 cm that involve greater than 50% of subcutaneous fat or with a sinus tract extending to bone, and when the bone marrow fluid signal region of interest measurement to joint fluid region of interest measurement ratio is greater than 53% [ 52 , 101 - 104 ]. Occasionally, there may be non-visualization of the cortical margins of the infected bone on the T1W images (known as the “ghost sign”), with the cortical margins visualized on both the fluid-sensitive and contrast-enhanced images, which may be helpful in the diagnosis of superimposed infection in a neuropathic foot [ 14 , 31 , 33 , 41 , 52 , 100 ].…”
Section: Diabetic Foot Infectionsmentioning
confidence: 99%